1994
DOI: 10.1007/bf00123834
|View full text |Cite
|
Sign up to set email alerts
|

The effects of changes in temperature or ionic strength on isolated rabbit and fish skeletal muscle thick filaments

Abstract: Although the skeletal muscles of different vertebrate species have been assumed to be generally similar, recent X-ray diffraction and mechanical studies have demonstrated differences in the responses of these muscles to changes in physiological conditions. X-ray diffraction studies have indicated that lowering the temperature and lowering ionic strength may affect the crossbridge arrangement of rabbit thick filaments. Similar X-ray diffraction studies on the structural effects of lowering ionic strength in fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
28
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 34 publications
9
28
2
Order By: Relevance
“…In warm-blooded animals, this adaptation to varying temperature is not usually a consideration, since these muscles do not normally operate physiologically at a temperature which would cause disordering. These results support our earlier conclusion (Kensler et al, 1994) that temperature is an important parameter which must be taken into account during studies of vertebrate skeletal muscle. Our results may also explain the relative paucity of previous studies on the structural arrangement of myosin in the chicken thick filament.…”
Section: Effects Of Temperaturesupporting
confidence: 82%
See 4 more Smart Citations
“…In warm-blooded animals, this adaptation to varying temperature is not usually a consideration, since these muscles do not normally operate physiologically at a temperature which would cause disordering. These results support our earlier conclusion (Kensler et al, 1994) that temperature is an important parameter which must be taken into account during studies of vertebrate skeletal muscle. Our results may also explain the relative paucity of previous studies on the structural arrangement of myosin in the chicken thick filament.…”
Section: Effects Of Temperaturesupporting
confidence: 82%
“…Both of these animals lose their cross-bridge order if the temperature of the muscle or filaments is lowered to low temperatures. In contrast, we have shown that in fish, a cold-blooded animal in which body temperature is not rigorously controlled, a similar lowering of temperature does not appear to cause a large loss of cross-bridge order (Kensler et al, 1994). This difference between warm-blooded and cold-blooded animals may relate to the physiological parameters under which the muscles operate, and the importance of the ordered relaxed cross-bridge arrangement.…”
Section: Effects Of Temperaturecontrasting
confidence: 39%
See 3 more Smart Citations